Time and Eternity in Biblical Thought - Pathrapankal, J. (Journal of Dharma, 1976)
When speaking about time and eternity as biblical concepts, it is important that we abandon our modern scientific or philosophical interpretations of them. We usually conceive of time and eternity as abstract dimensions: time as a frame within which events take place, as an empty space or as a prior entity which is subsequently filled out with the ordered succession of temporally distinct events; and eternity as an endless time or even as timelessness. But basic to the understanding of time and eternity as biblical concepts is the fundamental idea that here time is essentially understood from the point of view of time-content and eternity as the sum-total of God’s intervening in the history of salvation.